Optimalisasi Distribusi Dan Biaya Transportasi Rokok Troy Menggunakan Metode Stepping Stone Di Wilayah Papua - Gladis Dominica N; Joi Rosalina Raweyai; Maria Monalisa Gloria Bebari; Sharon Telvie Kondy; Dina A M Hombore; Heru Sutejo (Tamilis Synex: Multidimensional Collaboration, 2025)
Efficient logistics distribution is a significant challenge in Papua, especially for products that are in high demand such as Troy cigarettes. This study focuses on optimizing the distribution process from two central warehouses—Abepura and Kotaraja—to eleven destination points throughout Papua. The initial distribution plan was created using the Least Cost method to identify the minimum cost allocation. This allocation was then evaluated using the Stepping Stone method to measure its optimality and efficiency. The results of the analysis showed a total distribution cost of IDR9,900,000, with no negative opportunity cost values ​​found in the evaluation. This indicates that the initial allocation was optimal. The workload was evenly distributed, with each warehouse supplying 100 of the total 200 slops. The results of the study stated that the incorporation of optimization methods into research operations can significantly reduce logistics costs and improve delivery efficiency, especially in areas with complex geographic and transportation challenges. Companies are advised to apply this approach regularly and update data costs to maintain the accuracy of future logistics planning.